Mathematics Literacy Based on Students’ Self-efficacy By DAPIC Problem-Solving Realistic Approach With EDMODO-assisted (Universitas Negeri Semarang, 2022)
Mathematical literacy is one of the important fundamental life skills, therefore mathematics teaching must lead to mathematical literacy. Realistic Approach, using real-world problems as a starting point for learning and developing mathematical concepts. The collaborative learning of DAPIC Problem-Solving Realistic approach with Edmodo-assisted to improve mathematical literacy, gives students the opportunity to build their own mathematical knowledge through teacher guidance. This study aims to describe the ability of mathematical literacy in terms of students' self-efficacy in learning DAPIC Problem-Solving Realistic approach assisted by Edmodo. This type of research is a mixed method type of concurrent embedded design. The research subjects were students of class IX SMP Eka Sakti Semarang. The results obtained from the DAPIC Problem-Solving Realistic approach assisted by Edmodo on mathematical literacy, that students with high self-efficacy can master the seven components of the literacy process well, students with moderate self-efficacy are able to achieve well the components of communication, mathematizing, and mathematical using skills. tools, but weak in other literacy process skills. While students with low self-efficacy, five aspects can be mastered although not optimally, but have not been able to master the Communication and Mathematizing aspects.